Examining Lives in Context: Perspectives on the Ecology of Human Development.
DOI: 10.1037/10176-012
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative parenting and adolescent adjustment: An ecological journey.

Abstract: in collaboration with B. Bradford Brown and Sanford M. Dornbusch he impetus for much of the research presented in this chapter can be T traced to a specific conversation between Laurence Steinberg and Urie Bronfenbrenner in a hotel lobby in Kansas City, at the 1989 meetings of the Society for Research in Child Development.Earlier that day, our research group had made its first presentation from this project, on the impact of authoritative parenting on adolescent achievement (Mounts, Lamborn, & Steinberg, 1989)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

39
511
5
17

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 474 publications
(576 citation statements)
references
References 33 publications
39
511
5
17
Order By: Relevance
“…1 Socioeconomic status was based on both the participant's as well as a collateral's response to mother's and father's level of education. 2 The maximum response given by either the participant or collateral was used and an average was calculated as previous research has shown that parental education may be the most stable component of a family's social class (Steinberg, Mounts, Lamborn, & Dornbusch, 1991). Response options ranged from (1) some graduate/professional school to (6) grade school or less, with low scores being indicative of higher educational attainment.…”
mentioning
confidence: 99%
“…1 Socioeconomic status was based on both the participant's as well as a collateral's response to mother's and father's level of education. 2 The maximum response given by either the participant or collateral was used and an average was calculated as previous research has shown that parental education may be the most stable component of a family's social class (Steinberg, Mounts, Lamborn, & Dornbusch, 1991). Response options ranged from (1) some graduate/professional school to (6) grade school or less, with low scores being indicative of higher educational attainment.…”
mentioning
confidence: 99%
“…Os filhos de pais autoritativos têm sido associados sempre a aspectos positivos como melhor desempenho nos estudos (Steinberg, Darling & Fletcher, 1995;Cohen & Rice, 1997), uso de estratégias adaptativas (Aunola, Stattin & Nurmi, 2000), maior grau de otimismo (Weber, Viezzer & Brandenburg, 2002). Enfim, filhos de pais autoritativos são vistos como socialmente e instrumentalmente mais competentes do que os filhos de pais não autoritativos (Darling, 1999).…”
unclassified
“…Esta conceptualización reflejaba dos procesos subyacentes: el número y tipo de demandas hechas por los padres y la contingencia del refuerzo parental. Estudios posteriores (Dornbush, Ritter, Leiderman, Roberts & Fraleigh, 1987;Maccoby & Martins, 1983) expandieron la formulación de Baumrind y documentaron ampliamente los efectos de la responsividad y demanda parental (Steinberg, Darling, Fletcher, Brown & Dornbusch, 1995;Steinberg et al, 1991;Steinberg, Lamborn, Darling, Mounts & Dornbusch, 1994) y de las prácticas parentales -particularmente el monitoreo parental-en el desarrollo de niños y adolescentes (Dishion & McMahon, 1998;Stevenson & Baker, 1987).…”
unclassified
“…Los resultados de los estudios que han utilizado el estilo parental, en su mayoría, han sido robustos, en particular, la asociación entre calidez parental y resultados positivos en niños de diferentes culturas (Fletcher, Steinberg & Williams-Wheeler, 2004;Steinberg, 2001;Steinberg et al, 1991). No obstante, persisten algunas interrogantes respecto de la manera apropiada de medir el estilo parental (Darling & Toyokawa, 1997) y las características de algunas prácticas (e.g., monitoreo, Fletcher et al, 2004;Soenens & Vansteenkiste, 2005;, así como preguntas relativas a la capacidad de generalización de los resultados en diferentes poblaciones (Vazsonyi, Hibbert & Snider, 2003).…”
unclassified
See 1 more Smart Citation